LED red light therapy for relief of primary dysmenorrhea: An open, single-group target value clinical trial - Bin Yi; Dandan Wang; Ling Wei; Jun He; Qian Yu; Lei Wu; Yilin Wang; Yajuan Wang; Nan Song; Li Guo (PLOS One, 2026)
Objective To evaluate the efficacy and safety of LED red light therapy in alleviating primary dysmenorrhea. Methods A total of 119 patients with primary dysmenorrhea were enrolled in 2022. The intervention was LED red light therapy administered 7 days before menstruation. Clinical outcomes were assessed after three menstrual cycles. Results After three cycles of treatment, the mean reduction rate in the Visual Analog Scale (VAS) score was 63.62%. The overall effective rate of the device was 98.32%. The total score of the COX Menstrual Symptom Scale decreased by 72.93%, with specific reductions of 72.55% in symptom severity and 73.26% in pain duration. No severe adverse events were reported during the trial. Only one adverse event (0.84%) was considered device-related. Conclusion LED red light therapy is safe and effective for the treatment of primary dysmenorrhea. Trial registration ChiCTR2600116460 .